Sex-Differences in Discontinuation of Statin Treatment in Cancer Patients the Year before Death - Gabriella Frisk; Helena Bergström; Maria Helde Frankling; Linda Björkhem-Bergman (MDPI AG, 2021)
Statin treatment is often terminated in patients with advanced cancer but guidelines for statin discontinuation are still lacking. The aim of this study was to investigate sex-differences in time-points of statin discontinuation in patients with advanced cancer. Medical records from 1535 deceased patients enrolled at a Palliative Home Care Unit were reviewed. A total of 149 patients (42 women and 107 men) who were diagnosed with cancer, and were treated with statins one year before death, were identified. Statin treatment was terminated earlier in women than in men, 3.0 months prior to death (IQR 0.88-7.25) as compared to 1.5 months (IQR 0.5-4.0) (p < 0.05), respectively. In a longitudinal analysis there was a significant difference between men and women still on statin treatment at all studied time-points, 9, 6, and 3 months before death (p < 0.05), where women terminated statin treatment earlier in the disease trajectory. Baseline demographics were similar between the sexes except that more men than women had a history of previous cardiovascular events (p < 0.01). However, neither the indication for statin treatment, i.e., primary prevention versus secondary prevention, nor age could explain the sex-difference in statin discontinuation. There was no difference in cardiovascular events or mortality between men and women after statin discontinuation.